Gregor and the Prophecy of Bane - Collins, Suzanne (Collins, Suzanne. Underland chronicles, 2013)
Eleven-year-old Gregor returns to the world beneath New York City to rescue his kidnapped sister, Boots, and fulfill a prophecy that will restore peace to the people, bats, rats, cockroaches, and spiders who populate the underworld.